(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
Italian children’s mythology has a rather recent literary and editorial history: the first book of this type was published in 1911 and was Stories of Greece and the Barbarians by Laura Cantoni Orvieto. Books of myths for young readers have multiplied and have enjoyed a good success since then. It should be noted that this genre of storytelling for children had women as the main writers and protagonists of its creation and diffusion. In addition to the aforementioned Cantoni Orvieto – who is a very important figure in Italian children’s literature – it should be noted Luisa Banal, Mary Tibaldi Chiesa, Rosa Calzecchi Onesti and, nowadays, Beatrice Masini. These authors managed to enhance the female dimension of mythology, giving voice to the women, heroines and goddesses of ancestral tales who, for a long time, were placed on the margins of those ancient stories. Furthermore, even a very important children’s author like Gianni Rodari, through myths, was able to talk about the need for female emancipation.